NGSEP (Next Generation Sequencing Eclipse Plugin) - Cruz, Daniel Felipe; Hoz, Juan Fernando de la; Perea, Claudia Samantha; Quintero, Juan Camilo; Duitama, Jorge (2014)
NGSEP (Next Generation Sequencing Eclipse Plugin), an integrated framework for analysis of high throughput sequencing reads. The main functionality of NGSEP is the variants detector, which allows to make simultaneous discovery of SNVs, indels, and CNVs. NGSEP also provides a user interface for bowtie2 to perform mapping to the reference genome and other utilities such as alignments sorting, merging of variants from different samples, and functional annotation of variants. NGSEP is based on Eclipse which is one of the leading development environments for Java. Note: Since we offer different distribution alternatives for different kinds of users, the quick download (green) button may not lead you to the version of the product that you need. Please visit the web page to choose the distribution of NGSEP that better suits your data analysis environment.